Identifying and modelling complex workflow requirements in web applications - Urbieta, Mario Matías (2012)
Workflow plays a major role in nowadays business and therefore its requirement elicitation must be accurate and clear for achieving the solution closest to business's needs. Due to Web applications popularity, the Web is becoming the standard platform for implementing business workflows. In this context, Web applications and their workflows must be adapted to market demands in such a way that time and effort are minimize. As they get more popular, they must give support to different functional requirements but also they contain tangled and scattered behaviour. In this work we present a model-driven approach for modelling workflows using a Domain Specific Language for Web application requirement called WebSpec. We present an extension to WebSpec based on Pattern Specifications for modelling crosscutting workflow requirements identifying tangled and scattered behaviour and reducing inconsistencies early in the cycle.